Penegakan Hukum Keimigrasian Terhadap Penyalahgunaan Visa Izin Tinggal Warga Negara Asing - Sandi Pratama Putra; Muhammad Findra Rizhaldi; Muhammad Fido Brilian (Universitas Muhammadiyah Sumatera Utara, 2022)
Act No. 6 of 2011 Article 38: Visit Visa is granted to Foreigners who will travel to the Territory of Indonesia in the framework of a visit to government, education, socio-cultural, tourism, business, family, journalistic, or stopover to continue the trip to the country. The research method used is normative juridical. The results showed that supervision of foreigners is carried out according to Article 66 paragraph (2) of Act No. 6 of 2011 on Immigration to supervise the activities of foreigners living in the territory of Indonesia, whether visiting, staying temporarily or settling. After being granted the application, the next supervision is in the form of checking administrative completeness such as passports and visas, each foreigner must provide the necessary information about the identity of themselves and or their family, report in case of changes in civil status (changes involving marriage, divorce, death, the birth of children, moving jobs and quitting work), as well as changes in the address of their existence at the Airport Immigration Checkpoint or other access such as ports. Violations of administrative law such as overstay will be processed also with immigration administrative actions outside the judicial process which is administrative sanctions imposed by immigration officials against foreigners outside the judicial process